2013
DOI: 10.1111/cts.12089
|View full text |Cite
|
Sign up to set email alerts
|

Publication Track Records as a Metric of Clinical Research Training Effectiveness

Abstract: Clinical research training programs exist across the country, but no quantitative studies have been performed to evaluate the effectiveness of these programs. The goal of this study was to evaluate the success of the clinical research training program at the University of Cincinnati by comparing the publication histories of pediatric fellows who graduated from the clinical and translational research master of science (MS) degree programs between 1995 and 2011 with fellows who did not pursue an MS degree. Among… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 33 publications
(34 reference statements)
0
14
1
Order By: Relevance
“…We used logistic regression to evaluate the effect of graduating from the MSCTR on fellows' likelihood of receiving at least one grant award. We also evaluated the effect of the MSCTR on fellows' likelihood of obtaining at least one grant award by different type (K‐, R‐, and M‐series), and included age and sex as covariates, since past research has found these can be significant . We analyzed the amount of time to obtaining one's first grant by using a Kaplan–Meier plot and a Cox proportional hazards regression model with age and sex as covariates.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We used logistic regression to evaluate the effect of graduating from the MSCTR on fellows' likelihood of receiving at least one grant award. We also evaluated the effect of the MSCTR on fellows' likelihood of obtaining at least one grant award by different type (K‐, R‐, and M‐series), and included age and sex as covariates, since past research has found these can be significant . We analyzed the amount of time to obtaining one's first grant by using a Kaplan–Meier plot and a Cox proportional hazards regression model with age and sex as covariates.…”
Section: Methodsmentioning
confidence: 99%
“…In one study, using an alumni survey, Goldhamer et al found that success in obtaining NIH grant funding is associated with starting a training program at a younger age, being a generalist, and successfully publishing projects emanating from coursework. Recently, we reported findings from a study that compared publication track records of pediatric fellows who graduated from our MS program versus comparable pediatric fellows who did not get the MS degree, showing that MS graduates publish more first‐authored articles, and more articles overall, than their counterparts . Additionally, men in the non‐MS group out‐published their women colleagues, but the gender gap was absent in the MS group.…”
Section: Introductionmentioning
confidence: 95%
“…Whilst the minimum requirement for the number of surgical procedures and fellows' surgical outcomes has received much attention, there are no data on the outcomes of research training during ophthalmic subspecialty fellowship. The goal of this study was to evaluate the publication track record of fellows in Western Australia (WA) over a period of 28 years as a metric of clinical research training during ophthalmic subspecialty training and to establish a reasonable target for the number of research publications that can be expected from fellows during and after their fellowship training. A secondary objective was to examine whether publication track record prior to commencing fellowship has an impact on future bibliometric.…”
Section: Comparison Between Wa and Rveeh Fellow Publication Outputmentioning
confidence: 99%
“…All 62 CTSIs offer formal postdoctoral training programs, 33 of which offer clinical research master's degree programs to medical students . Although program descriptions and outcomes data have been published for other common dual‐degree programs (MD/PhD, MD/MPH, MD/MBA), published data regarding MSCI programs are sparse, particularly in the contexts of medical student MD/MSCI training . Experience sharing is important for designing new programs, improving established programs, and identifying solutions to structural challenges.…”
Section: Background: Educating Physician Scientistsmentioning
confidence: 99%
“…1 Although program descriptions and outcomes data have been published for other common dualdegree programs (MD/PhD, MD/MPH, MD/MBA), published data regarding MSCI programs are sparse, particularly in the contexts of medical student MD/MSCI training. [2][3][4][5][6][7][8] Experience sharing is important for designing new programs, improving established programs, and identifying solutions to structural challenges. Here we describe our MD/MSCI program to promote similar program development and to encourage an ongoing dialogue about educating the next generation of translational researchers.…”
Section: Background: Educating Physician Scientistsmentioning
confidence: 99%